Evaluation system and method for dissolution quality of binder solution for secondary battery electrodes and method for producing electrode slurry for secondary battery

By measuring the accumulated filtration amount and flow reduction rate of the adhesive solution, accurately evaluating its dissolution quality, the problem of unstable electrode quality in the prior art was solved, and the quality of electrode slurry was improved.

CN115428195BActive Publication Date: 2025-02-11LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280003652.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-21
Publication Date
2025-02-11
Estimated Expiration
2042-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to accurately and quantitatively evaluate the dissolution quality of the adhesive solution for secondary battery electrodes, resulting in unstable electrode quality.

Method used

The dissolution quality is quantitatively evaluated by measuring the filtration amount accumulated in the first time period of the adhesive solution and/or the flow reduction rate relative to the initial flow rate after the second time period, and the high-quality adhesive solution is selected based on the measured value. Used to make electrode slurry.

Benefits of technology

Accurate evaluation of the dissolution quality of the adhesive solution is achieved, the quality characteristics of the electrode slurry are improved, and the surface defects, viscosity and adhesive strength of the electrode are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115428195B_ABST
    Figure CN115428195B_ABST
Patent Text Reader

Abstract

According to the evaluation system and method of dissolution quality of a secondary battery electrode binder solution, the quality of a secondary battery electrode can be improved by preparing electrode slurry with a binder solution having a cumulative filtration amount greater than a predetermined amount or a flow reduction rate less than a predetermined level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an evaluation system and an evaluation method for the quality of a binder solution for secondary battery electrodes. More particularly, the present invention relates to an evaluation system and an evaluation method for dissolution quality, which can evaluate the dissolution quality by quantitatively evaluating a parameter indicating a change in the flow rate of the binder solution over time.

[0002] Furthermore, the present invention relates to a method for producing an electrode slurry for a secondary battery, the method being capable of improving the quality of an electrode by applying a binder solution whose dissolution quality has been evaluated.

[0003] This application claims priority to and the benefit of Korean Patent Application No. 10-2021-0041337, filed on March 30, 2021, and Korean Patent Application No. 10-2021-0041343, filed on March 30, 2021, the disclosures of which are incorporated herein by reference in their entirety. Background Art

[0004] With the technological development and increase in demand for mobile phones, automobiles, and energy storage devices, the demand for batteries as energy sources is rapidly increasing, and among these secondary batteries, lithium secondary batteries have been widely studied and also commercialized and used in various fields.

[0005] The electrode used in the lithium secondary battery is formed by applying a mixture layer containing active materials on an electrode substrate composed of a metal foil, wherein the mixture layer is formed by applying a positive electrode or a negative electrode slurry on the electrode substrate and drying the resulting slurry. Such an electrode slurry is manufactured by mixing a solid component containing a positive / negative electrode active material, a conductive material, etc. with a binder solution and drying.

[0006] Binders are used to attach active materials to each other or to an electrode substrate to improve the bonding strength of the electrode and to adjust the viscosity of the slurry. Binders are used in the form of a binder solution dissolved in a predetermined solvent and mixed with active materials, conductive materials, etc. The dissolution quality of the binder affects the quality characteristics of the electrode slurry or electrode. For example, in the case of a binder with poor dissolution quality such as CMC or PVDF, various problems may occur, such as increased slurry viscosity and surface defects of the electrode coating. The dissolution quality of the binder depends on the extent to which the undissolved matter in the binder solution can be reduced.

[0007] In general, in order to confirm the dissolution quality of the adhesive solution, a method of simply visually inspecting the adhesive that is not very soluble in the solution or applying the adhesive solution to an OHP film using a blade of a predetermined thickness and visually inspecting the number of impurities on the film is used. In addition, a method of filtering the solution through a nylon mesh filter to count the number of impurities in the filter is applied.

[0008] However, the method of observing the amount of impurities on the membrane has the disadvantages that it is difficult to grasp the overall quality of the solution due to the small amount of sample, and the measurement accuracy is reduced because external impurities such as dust may enter and cannot be distinguished from undissolved impurities. In addition, since the evaluation is performed with the naked eye, there are problems such as large errors caused by the evaluator.

[0009] In the method of measuring the amount of impurities using a mesh filter, impurities originating from the filter itself may be added to the filter. In addition, bubbles are generated during the filtration process, and impurities are trapped in the bubbles. In addition, during the filtration process, there are cases where the solute in the solution is precipitated and separated from the solvent due to the addition of water. Therefore, there is a disadvantage that the reproducibility and accuracy of the dissolution quality evaluation are very low.

[0010] As described above, when the dissolution quality of the binder solution is not accurately evaluated, the quality of the secondary battery electrode slurry or electrode may vary greatly depending on the dissolution quality thereof even though a binder solution in which the same content of the binder is dissolved in the solvent is used.

[0011] Therefore, there is a need to develop a technology capable of improving electrode quality by accurately quantitatively evaluating the dissolution quality of a binder solution used to manufacture secondary battery electrodes.

[0012] [Related technical literature]

[0013] [Patent Document]

[0014] Korean Unexamined Patent Application Publication No. 10-2017-0111722 Summary of the invention

[0015] Technical issues

[0016] In order to solve the above problems, the present invention aims to provide an evaluation system for the dissolution quality of a binder solution for secondary battery electrodes, which can quantitatively evaluate the dissolution quality using the cumulative filtration amount and / or flow reduction rate as parameters representing the change in flow rate of the binder solution over time; and its evaluation method.

[0017] Furthermore, the present invention aims to provide a method for manufacturing an electrode slurry for a secondary battery, the evaluation method comprising preparing the electrode slurry using a binder solution having a cumulative filtration amount of a predetermined level or more or a flow reduction rate of a predetermined level or less.

[0018] Technical Solution

[0019] In order to solve the above problems, one aspect of the present invention provides a system for evaluating the dissolution quality of a binder solution for a secondary battery electrode, the system comprising a pressure vessel containing a binder solution; a pressure medium source for supplying a pressure medium of a predetermined pressure to the pressure vessel; a filter connected to the pressure vessel through a conduit; and a flow measurement component for measuring at least one of a) and b) of the binder solution passing through the filter when the binder solution in the pressure vessel is transferred to the filter by the pressure medium supplied to the pressure vessel and filtered:

[0020] a) cumulative filtration volume during the first period of time; and

[0021] b) The flow rate reduction rate after the second time period relative to the initial flow rate.

[0022] In one example, the conduit may extend into the pressure vessel, and an end of the conduit may be mounted near a bottom of the pressure vessel.

[0023] In one example, the filter can be an in-line filter installed in series with the conduit.

[0024] Specifically, the in-line filter includes a filter member, an elastic member pressurizing the filter member, and a housing accommodating the filter member and the elastic member.

[0025] Another aspect of the present invention provides a method for evaluating the dissolution quality of a binder solution for secondary battery electrodes, the method comprising: adding a predetermined amount of a binder solution to a pressure vessel; transferring the binder solution to a filter by supplying a pressure medium of a predetermined pressure to the pressure vessel; filtering the binder solution through the filter; and measuring at least one of the following a) and b) for the binder solution passing through the filter:

[0026] a) cumulative filtration volume during the first period of time; and

[0027] b) The flow rate reduction rate after the second time period relative to the initial flow rate.

[0028] In one example, the binder solution may be stored and transferred from the pressure vessel in a system closed to the outside until a) the cumulative filtration amount or b) the flow reduction rate is measured.

[0029] In another example, the binder solution may be transferred to the filter along a conduit extending into the pressure vessel and having one end mounted near the bottom of the pressure vessel.

[0030] The binder solution may be filtered through an in-line filter installed in series with the conduit.

[0031] In one example, the binder as a solute of the binder solution can be one or more selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, hydroxyethyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, polytetrafluoroethylene (PTFE), nitrile rubber, styrene-butadiene rubber (SBR) and acrylic rubber.

[0032] The solvent of the adhesive solution may be:

[0033] One or more organic solvents selected from N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone and dimethylacetamide, or

[0034] water.

[0035] As a specific example, the binder solution may be a CMC solution obtained by dissolving a predetermined content of CMC in water, or a PVDF solution obtained by dissolving a predetermined content of PVDF in NMP.

[0036] In one example, the cumulative filtration volume in the first time period may be the cumulative filtration volume within 10 minutes after filtration.

[0037] In one example, the flow rate reduction rate relative to the initial flow rate after the second period of time may be the flow rate reduction rate relative to the initial flow rate after 2 hours.

[0038] Another aspect of the present invention provides a method for manufacturing an electrode slurry for a secondary battery, the method comprising: preparing a binder solution that satisfies at least one of a1) and b1) according to a method for evaluating the dissolution quality of a binder solution for a secondary battery electrode; and manufacturing an electrode slurry by mixing an electrode active material and a conductive material with the binder solution:

[0039] a1) cumulative filtration volume in a first time period exceeding a predetermined volume; and

[0040] b1) a flow rate reduction rate relative to the initial flow rate after a second period of time below a predetermined value.

[0041] Beneficial Effects

[0042] According to the present invention, the quality of an electrode for a secondary battery can be improved by preparing an electrode slurry using a binder solution having a cumulative filtration amount of a predetermined amount or more or a flow rate reduction rate of a predetermined value or less.

[0043] For example, surface defects of an electrode can be improved by manufacturing an electrode slurry using a binder solution having a cumulative filtration amount of a predetermined amount or more.

[0044] In addition, the viscosity of the electrode slurry can be reduced by manufacturing the electrode slurry using a binder solution having a flow reduction rate of a predetermined value or less. In addition, the bonding strength of the electrode manufactured using the electrode slurry can be increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 : is a diagram showing the configuration of an evaluation system for the dissolution quality of a secondary battery electrode binder solution.

[0046] Figure 2 is a cross-sectional view of a filter as a component of the system.

[0047] Figure 3 The amount of foreign matter in the filter obtained by applying the evaluation method using a conventional nylon mesh filter is shown.

[0048] Figure 4 : is a graph showing the change over time of the flow rate reduction rate of the binder solution filtered by the dissolution quality evaluation system of the present invention.

[0049] Figure 5 is a graph showing the adhesive strength of an electrode manufactured by the method for preparing an electrode slurry of the present invention. DETAILED DESCRIPTION

[0050] The present invention will be described in detail below. Prior to this, the terms and words used in the specification and claims should not be interpreted as limited to the general or dictionary term meanings, but should be interpreted based on the concept that the inventor has appropriately defined the terms in order to explain the principles of the present invention in the best way with the meaning and concept of the technical concept according to the present invention.

[0051] In this specification, it should be understood that the terms "comprise", "include" or "have" are intended to indicate the presence of the characteristics, quantities, steps, functions, constituent elements or parts or combinations thereof described in the specification, but do not exclude the possibility of the presence or addition of one or more characteristics, quantities, steps, functions, constituent elements, parts or combinations thereof. In addition, when a portion of a layer, film, zone or plate is configured "on" another portion, this includes not only the case where a portion is configured "directly" "on" another portion, but also the case where a third portion is interposed therebetween. Conversely, when a portion of a layer, film, zone or plate is configured "under" another portion, this includes not only the case where a portion is configured "directly" "under" another portion, but also the case where a third portion is interposed therebetween. In addition, in the present application, "on..." includes not only the case where it is configured on the upper portion, but also the case where it is configured on the lower portion.

[0052] Figure 1 : is a diagram showing the configuration of an evaluation system for the dissolution quality of a secondary battery electrode binder solution.

[0053] The dissolution quality evaluation system 100 of the secondary battery electrode adhesive solution of the present invention includes: a pressure vessel 10 containing an adhesive solution 1; a pressure medium source 20 that supplies a pressure medium of a predetermined pressure to the pressure vessel 10; a filter 30 connected to the pressure vessel 10 through a conduit 12; and a flow measurement component 40 that measures at least one of the following a) and b) for the adhesive solution passing through the filter 30 when the adhesive solution in the pressure vessel 10 is transferred to the filter and filtered by the pressure medium supplied to the pressure vessel 10.

[0054] a) cumulative filtration volume during the first period of time; and

[0055] b) The flow rate reduction rate after the second time period relative to the initial flow rate.

[0056] As a raw material for electrode slurry for secondary batteries, the binder is used to attach active materials to each other or to the surface of the current collector and to increase the bonding strength of the coated electrode. The binder is mixed with the electrode active material and the conductive material in the form of a binder solution in which the solid component of the binder is dissolved in a predetermined solvent to produce the electrode slurry. However, when the binder contained in the binder solution remains in the form of fine undissolved matter such as microgel without being completely dissolved, the undissolved portion may not be able to play the proper role of the binder. In this part, electrode surface defects such as gray spots, pinholes or craters will appear, and in severe cases it will become an active material defect area, and the bonding strength of the electrode will decrease. In addition, the undissolved matter increases the viscosity of the electrode slurry, adversely affects the fluidity of the slurry and impairs the coating property when the electrode substrate is coated with the electrode slurry.

[0057] Therefore, although the dissolution quality of the binder solution for secondary battery electrodes is an important factor in improving electrode surface defects, coating properties of electrode slurry, and electrode adhesion, it has been difficult to accurately determine the dissolution quality in the past. In the present invention, before manufacturing the electrode slurry, in order to quantitatively evaluate the dissolution quality of the binder solution, a method of measuring the cumulative filtration amount in the first time period and / or the flow reduction rate relative to the initial flow after the second time period and evaluating the dissolution quality with the measured values ​​is introduced, wherein the cumulative filtration amount in the first time period and the flow reduction rate relative to the initial flow after the second time period are obtained by filtering the binder solution.

[0058] When there are a large number of impurities or undissolved matter in the adhesive solution, they are filtered by the filter, and the flow through the filter gradually decreases. When the adhesive solution is well mixed or the impurities in the solution are pre-filtered before passing through the filter, the content of undissolved matter in the solution is reduced, thereby reducing filter clogging and increasing the filtration amount. The cumulative filtration amount refers to the solution flow measured by accumulating the filtration amount of this solution in a specific time period. As described above, the more undissolved matter the solution contains, the less cumulative filtration amount is, and the less undissolved matter the solution contains, the more cumulative filtration amount is increased. Therefore, the dissolution quality of the adhesive solution can be quantitatively evaluated by measuring the cumulative filtration amount. When the quality of the adhesive solution can be accurately evaluated by the cumulative filtration amount, it is possible to select an adhesive solution with excellent dissolution quality and less undissolved matter, that is, an adhesive solution with a cumulative filtration amount of more than a predetermined amount. Because the cumulative filtration amount is a parameter that accumulates the filtration amount through the filter over time, that is, a parameter that indicates that the flow changes over time, it is necessary to specify the time of the cumulative filtration amount. In this specification, the time for measuring the cumulative filtration amount refers to the "first time period". When the "first time period" is short, the dissolution quality of the adhesive solution can be quickly determined.

[0059] In addition, the "predetermined amount or more of the first time period cumulative filtration amount" used herein refers to the cumulative filtration amount of the binder solution that can produce an electrode slurry with a desired quality. That is, the "predetermined amount or more of the first time period cumulative filtration amount" refers to the cumulative filtration amount used to determine that the binder solution has a dissolution quality that can contribute to the quality improvement of the electrode slurry. For example, when the electrode slurry is produced by mixing the electrode active material and the conductive material with the binder solution that is evaluated to have a predetermined amount or more of the first time period cumulative filtration amount and is effective in improving surface defects, viscosity of the electrode slurry, or electrode adhesion, an excellent electrode with improved quality can be obtained.

[0060] On the other hand, the flow reduction rate is also a parameter indicating that the flow changes over time, just like the cumulative filtration volume. In the present invention, the flow reduction rate refers to the ratio of the flow through the filter after a predetermined time to the initial flow through the filter. Therefore, the more undissolved matter the solution contains, the greater the flow reduction rate, and the less undissolved matter the solution contains, the less the flow reduction rate. An increase in the cumulative filtration volume means that the flow reduction rate of the solution passing through the filter decreases over time. That is, the flow reduction rate is inversely proportional to the cumulative filtration volume. The greater the cumulative filtration volume, the smaller the flow reduction rate, and the smaller the cumulative filtration volume, the greater the flow reduction rate.

[0061] The cumulative filtration amount or the flow reduction rate is a parameter indicating the change of flow rate over time, and when measured, the dissolution quality of the binder solution can be quantitatively evaluated. The cumulative filtration amount or the flow reduction rate can be selectively measured in consideration of the type or characteristics of the solution or the time required for measurement. In particular, when the flow reduction rate and the cumulative filtration amount are measured together, the dissolution quality of the binder solution can be more accurately and comprehensively evaluated.

[0062] Because the flow reduction rate is a parameter indicating that the flow changes over time, it is necessary to specify the time of initial flow, final flow and flow reduction. "The time of flow reduction" used in this article, i.e. the time of measuring the flow reduction rate, is referred to as "the second time period". When the "second time period" is short, the dissolution quality of the adhesive solution can be quickly determined. In addition, the initial flow refers to the flow through the filter within the initial predetermined time interval. For example, the flow of the solution through the filter within the first minute, i.e. the initial per minute flow, can be defined as the initial flow. In addition, the final flow refers to the flow through the filter within the predetermined time interval after the second time period. For example, when the second time period is 2 hours, the per minute flow after 2 hours after the initial flow measurement can be the final flow. The time interval can vary according to the type or characteristics of the solution.

[0063] In addition, the "rate of flow reduction relative to the initial flow after the second time period below a predetermined level" used herein refers to the rate of flow reduction of the binder solution capable of producing an electrode slurry having a desired quality. That is, the rate of flow reduction relative to the initial flow after the second time period below a predetermined level refers to the rate of flow reduction used to determine that the binder solution has a dissolution quality that can contribute to the improvement of the quality of the electrode slurry. For example, when an electrode slurry is prepared by mixing an electrode active material and a conductive material with a binder solution that is evaluated to have a flow reduction rate below a predetermined level and is effective in improving surface defects, viscosity of the electrode slurry, or electrode adhesion, an excellent electrode with improved quality can be obtained.

[0064] In order to accurately determine the dissolution quality of the binder solution, it is preferable to accurately measure the cumulative filtration amount or the flow reduction rate. When the binder solution is exposed to the external environment before and after the process of passing the binder solution through the filter to measure the cumulative filtration amount or the flow reduction rate, impurities may be added from the outside. In this case, it is difficult to accurately measure the cumulative filtration amount or the flow reduction rate because not only undissolved matter in the binder solution but also external impurities may adhere to the filter. Therefore, in Figure 1 In the illustrated evaluation system 100 for dissolution quality of a binder solution according to an example of the present invention, the binder solution 1 is stored and transferred in a closed system from a container 10 containing the binder solution 1 until the cumulative filtration amount and / or the flow reduction rate is measured.

[0065] like Figure 1 As shown, in one embodiment of the present invention, the adhesive solution 1 is contained in a pressure vessel 10 that is closed to the outside. The pressure vessel 10 refers to a closed container to which pressure is applied, and refers to a container that has pressure resistance and can withstand a predetermined pressure. For example, it is sufficient for the pressure vessel 10 to withstand the pressure even when a predetermined pressure is applied to the space inside the pressure vessel. That is, the pressure vessel 10 in the system 100 is a container with airtightness and pressure resistance, and is a container that can hold an adhesive solution for a secondary battery. The capacity of the pressure vessel can be appropriately selected within the range of the amount of adhesive solution required for filtration. For example, a pressure vessel with a capacity of about 20 kg can be used. The amount of adhesive solution contained in the pressure vessel can be appropriately selected within the capacity range of the pressure vessel. The pressure vessel 10 can be filled with, for example, 1 to 5 kg of solution.

[0066] When the pressure container 10 is filled with the solution 1, the solution in the pressure container 10 can be transferred to the outside by applying a constant pressure to the space above the solution. To this end, a supply line 22 capable of supplying a pressure medium from the outside and a solution discharge conduit 12 connected to a filter 30 are connected to the pressure container 10. As an embodiment, Figure 1 As shown, the solution discharge conduit 12 may extend into the pressure vessel 10, and the end of the conduit may be installed near the bottom of the pressure vessel. Therefore, a portion 12a of the solution discharge conduit is immersed in the adhesive solution 1. In this way, when the solution discharge conduit 12 is installed near the bottom of the pressure vessel 10, in the case where the solution is pushed toward the filter by applying pressure to the upper space of the solution in the pressure vessel, it is advantageous in that most of the solution can be transferred to the filter 30 even when the liquid level of the solution drops. An on / off valve 13 is installed in the solution discharge conduit 12 between the pressure vessel 10 and the filter 30. In addition, in order to measure the pressure in the pressure vessel 10, a pressure gauge 11 may be connected to the vessel and installed.

[0067] The pressurization of the pressure vessel 10 is mediated by a pressure medium from a pressure medium source 20. As the pressure medium, dry air or an inert gas that does not affect the physical and chemical properties of the adhesive solution can be used. In particular, nitrogen can be used as the pressure medium in terms of management and manufacturing costs. The pressure medium source 20, for example, a nitrogen source, can be a high-pressure nitrogen storage tank. Nitrogen at a predetermined pressure is supplied from the pressure medium source 20 to the pressure vessel through a supply line 22. An on / off valve 21 for controlling the flow of the pressure medium can be installed in the supply line 22.

[0068] The pressure medium has a predetermined pressure capable of transferring the binder solution 1 in the pressure container to the filter 30, which is higher than the pressure in the pressure container 10. For example, when the pressure medium is nitrogen, nitrogen with a pressure of about 1 to 7 bar can be delivered to the pressure container 10.

[0069] The filter 30 connected to the pressure vessel 10 through the conduit 12 is a so-called in-line filter installed in series with the conduit. The in-line filter is a filter installed by being connected to the conduit line, so that the solution flow through the conduit line is continuously transferred to the subsequent conduit through the filter. Therefore, by using the in-line filter 30, the binder solution passing through the conduit and the filter is not exposed to the outside, so there is an advantage in that contamination due to the external environment can be prevented during the filtration process for evaluating the dissolution quality.

[0070] Figure 2 is a cross-sectional view of a filter as a component of the system.

[0071] Figure 2 The filter 30 is an online filter, comprising a filter member 31, an elastic member 32 for pressurizing the filter member 31, and a housing 33 for accommodating the filter member 31 and the elastic member 32. The elastic member 32 is used to fix the filter member 31, and prevents solution leakage by making the filter member 31 in close contact with the housing. In addition, the filter 30 includes a gasket 34 for preventing solution leakage. The front and rear ends of the filter 30 are connected to the conduit. The pore size of the filter member 31 can be changed by considering the type of adhesive used, the flow rate of the solution, or the size of the undissolved matter. For example, a suitable filter with a pore size in the range of 0.5 to 100 μm can be selected. When the pore size is too large, the required sample amount increases, and there is a risk that the undissolved matter is not properly filtered and the dissolution quality cannot be accurately evaluated. When the pore size is small, the quality evaluation takes a long time due to the low filtration speed. Considering these points, it is recommended to select a filter with an appropriate pore size.

[0072] The flow rate of the binder solution 1 filtered through the filter 30 is measured in the flow measurement unit 40. The flow measurement unit 40 may include an electronic scale 41 for measuring the flow rate of the solution obtained by filtration, and a flow measurement unit 42 for measuring (calculating) the cumulative filtration amount and / or the flow rate reduction rate by the flow rate measured by the electronic scale 41. The electronic scale 41 may use a scale that satisfies the specification of, for example, a minimum display of 0.1 g and a maximum display of 6 kg or more. A container such as a beaker is mounted on the electronic scale 41, and the flow rate of the filtered binder solution dripped into the beaker can be measured.

[0073] The flow measurement component 40 can measure the cumulative filtration volume of the solution 1 filtered for a predetermined time. The cumulative filtration volume is the cumulative volume of the solution flow through the filter in the first time period. For example, the cumulative filtration volume (W10) of 10 minutes, the cumulative filtration volume (W20) of 20 minutes and the cumulative filtration volume (W30) of 30 minutes after passing through the filter can be calculated respectively. In order to shorten the dissolution quality evaluation time, the cumulative filtration volume (W10) is preferably used. However, according to the properties of the solution or adhesive, the dissolution quality can be evaluated with the cumulative filtration volume W20 or W30.

[0074] In addition, the flow measurement component 40 can measure the initial flow and the flow reduction rate after the second time period. The flow of the solution dripped into the beaker can be measured at fixed time intervals, and the average value is taken to obtain the flow rate per second of a specific time period. When the flow rate per second is obtained, the flow rate per minute (g / minute) and the initial flow rate can be obtained. The initial flow rate can be the initial flow rate per minute. Thus, the flow measurement component 42 can measure the initial flow of the filtered solution 1 and the flow reduction rate after the second time period.

[0075] The flow measurement component 42 may include predetermined software capable of automatically calculating the cumulative filtration amount and / or the initial flow rate during the first time period, and the flow rate reduction rate after the second time period.

[0076] The method for evaluating the dissolution quality of a binder solution for secondary battery electrodes according to the present invention comprises: injecting a predetermined amount of a binder solution into a pressure vessel; transferring the binder solution to a filter by supplying a pressure medium of a predetermined pressure to the pressure vessel; filtering the binder solution through the filter; and measuring at least one of the following a) and b) for the binder solution passing through the filter:

[0077] a) cumulative filtration volume during the first period of time; and

[0078] b) The flow rate reduction rate after the second time period relative to the initial flow rate.

[0079] By using a) and / or b), the dissolution quality of the binder solution can be evaluated.

[0080] For example, when measuring the cumulative filtration volume over the same period of time through filters of the same pore size, the dissolution quality of a solution having a larger cumulative filtration volume can be evaluated as being better than that of a solution having a smaller cumulative filtration volume.

[0081] Furthermore, when the flow reduction rate after passing through a filter of the same pore size for the same period of time is measured, it can be evaluated that the dissolution quality of a solution with a low flow reduction rate is better than that of a solution with a high flow reduction rate.

[0082] By using the evaluation system and method for dissolution quality according to the present invention, the dissolution quality of the binder solution can be quantitatively evaluated by measuring the cumulative filtration amount and / or flow reduction rate of each binder solution by repeating various tests according to the type and concentration of each binder solution.

[0083] In the step of measuring the cumulative filtration amount or the flow reduction rate, the adhesive solution is preferably stored and transferred from the container containing the adhesive solution in a system closed to the outside until the measurement. To this end, the adhesive solution is preferably contained in a pressure vessel closed to the outside, and the adhesive solution in the pressure vessel can be transferred to the filter along the conduit by applying a pressure medium of a predetermined pressure to the space in the pressure vessel. In this case, the adhesive solution can be transferred to the filter along the conduit extending into the pressure vessel and the end of which is installed near the bottom of the pressure vessel.

[0084] The binder as the solute of the binder solution can be one or more selected from the group consisting of: polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, polytetrafluoroethylene (PTFE), nitrile rubber, styrene-butadiene rubber (SBR) and acrylic rubber.

[0085] In addition, the solvent of the binder solution may be one or more organic solvents selected from N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, and dimethylacetamide, or water.

[0086] As a specific example, the binder solution may be a CMC solution obtained by dissolving a predetermined amount of CMC in water. The CMC solution is mainly used as a binder solution for negative electrode slurry.

[0087] As another example, the binder solution may be a PVDF solution obtained by dissolving a predetermined amount of PVDF in NMP. The PVDF solution is mainly used as a binder solution for positive electrode slurry.

[0088] The evaluation system and method for dissolution quality according to the present invention can be used to evaluate the dissolution quality of a binder solution for a positive electrode or a negative electrode.

[0089] On the other hand, a method for producing an electrode slurry for a secondary battery includes:

[0090] preparing a binder solution satisfying at least one of the following conditions a1) and b1) according to a method for evaluating dissolution quality of a binder solution for secondary battery electrodes; and

[0091] An electrode slurry is manufactured by mixing an electrode active material and a conductive material with the binder solution.

[0092] a1) cumulative filtration volume in a first time period exceeding a predetermined volume; and

[0093] b1) a flow rate reduction rate relative to the initial flow rate after a second period of time below a predetermined value.

[0094] That is, according to the method of preparing the electrode slurry, it can be, for example, Figure 1 The dissolution quality evaluation system measures the cumulative filtration amount in the first time period and the flow rate reduction rate after the second time period, thereby evaluating the dissolution quality of the corresponding adhesive solution. Therefore, a high-quality adhesive solution having a cumulative filtration amount greater than a predetermined amount and / or a flow rate reduction rate less than a predetermined value can be selected (prepared) from the adhesive solutions whose dissolution quality has been evaluated.

[0095] The electrode slurry may be prepared by mixing the electrode active material and the conductive material with a high-quality binder solution, thereby improving the quality characteristics of the electrode slurry.

[0096] The electrode active material may include a predetermined positive electrode active material and a negative electrode active material. The positive electrode active material may be a lithium-containing oxide, and the lithium-containing oxide may be a lithium-containing transition metal oxide.

[0097] For example, the lithium-containing transition metal oxide may be any one selected from the group consisting of: Li x CoO2(0.5 <x<1.3)、Li x NiO2(0.5 <x<1.3)、Li x MnO2(0.5 <x<1.3)、Li x Mn2O4(0.5 <x<1.3)、Li x (Ni a Co b Mn c )O2(0.5 <x<1.3、0<a<1、0<b<1、0<c<1、a+b+c=1)、Li x Ni1-y Co y O2 (0.5 < x < 1.3, 0 < y < 1), Li x Co 1-y Mn y O2 (0.5 < x < 1.3, 0 ≤ y < 1), Li x Ni 1-y Mn y O2 (0.5 < x < 1.3, 0 ≤ y < 1), Li x (Ni a Co b Mn c )O4 (0.5 < x < 1.3, 0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), Li x Mn 2-z Ni z O4 (0.5 < x < 1.3, 0 < z < 2), Li x Mn 2- z Co z O4 (0.5 < x < 1.3, 0 < z < 2), Li x CoPO4 (0.5 < x < 1.3) and Li x FePO4 (0.5 < x < 1.3), or a mixture of two or more thereof. In addition, the lithium-containing transition metal oxide may be coated with a metal such as aluminum (Al) or its metal oxide. In addition, in addition to the lithium-containing transition metal oxide, one or more of sulfides, selenides, and halides may be used.

[0098] The negative electrode active material may include a carbon material, lithium metal, silicon, or tin. When a carbon material is used as the negative electrode active material, it may be low-crystalline carbon or high-crystalline carbon. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include high-temperature calcined carbon such as natural graphite, floating graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbeads, mesophase pitch, and coke derived from petroleum or coal tar pitch.

[0099] There is no particular limitation on the conductive material as long as it has conductivity and does not cause chemical changes in the battery. Examples of the conductive material may include graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal cracking carbon black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives.

[0100] The electrode paste may be a positive electrode paste or a negative electrode paste.

[0101] Modes for Carrying Out the Invention

[0102] Examples will be provided below to specifically explain the present invention, but the present invention is not limited to the following examples.

[0103] Comparative Example 1

[0104] 1.3% CMC solution was prepared by adding a specific amount of CMC to distilled water. A pitched paddle was selected as the mixer blade and stirring was performed by varying the stirring time. To compare the dissolution quality, CMC solutions were prepared by filtering through a filter with a pore size of 50 or 30 μm before measuring the cumulative filtration amount or without any filtration.

[0105] The dissolution quality of the CMC solution prepared as above was evaluated by a conventional evaluation method. That is, after applying each CMC solution to a 5×5 cm OHP film to a thickness of 200 μm using a doctor blade, the results of visually inspecting the amount of impurities on the film are shown below. The numbers after “±” in Table 1 indicate the deviation of the amount of impurities obtained by different observers according to the conventional method.

[0106] [Table 1]

[0107] Mixing time (minutes) Whether to filter Microgel (quantity) 60 × 40±10 60 50μm 35±10 120 × 35±5 120 50μm 20±5 180 × 25±5 180 50μm 15±5 240 × 5±3 240 30μm 7±2

[0108] As shown in Table 1, as the mixing time increases, the amount of impurities tends to decrease. However, when the mixing time is 240 minutes, the filtered solution has a larger amount of impurities. In addition, as shown above, since there is a deviation depending on the observer and the measured amount of impurities is not constant, the dissolution quality of the CMC solution cannot be accurately quantitatively evaluated.

[0109] Example 1

[0110] A 1.3% CMC solution was prepared under the same conditions as in Comparative Example 1 by mixing and filtering.

[0111] use Figure 1 The system shown filters the prepared CMC solution to measure the cumulative filtration volume (W10) in 10 minutes. The online filter used to measure the cumulative filtration volume is an F1 series online filter (manufactured by Hy-Lok Co., Ltd.), and the filter member used herein is a stainless steel deep filter. The pore size of the online filter used herein is 10 μm. The flow rate of the filtered solution is measured with an electronic scale (GP30K electronic scale, AND company), and the measurement result of the cumulative filtration volume in 10 minutes is compared with the result of Comparative Example 1.

[0112] [Table 2]

[0113] Mixing time (minutes) Whether to filter Microgel (quantity) Cumulative filtration volume (g) 60 × 40±10 454 60 50μm 35±10 585 120 × 35±5 681 120 50μm 20±5 834 180 × 25±5 907 180 50μm 15±5 1020 240 × 5±3 1408 240 30μm 7±2 1700

[0114] As shown in Table 2, as the mixing time increases, the cumulative filtration amount increases. In addition, this trend appears in a very quantitative manner, and there is no deviation depending on the observer. Therefore, it can be seen that the dissolution quality of the secondary battery electrode binder solution can be accurately quantitatively evaluated by the cumulative filtration amount in the first time period (10 minutes).

[0115] Example 2

[0116] In order to evaluate the defect characteristics of the electrode surface based on the cumulative filtration amount (dissolution quality) of the CMC solution, CMC solutions of the same concentration (1.3%) with different cumulative filtration amounts were prepared. CMC solutions with different cumulative filtration amounts were prepared by adjusting the presence or absence of prefiltration and the dissolution time.

[0117] The negative electrode slurry was prepared by preparing graphite as a negative electrode active material, carbon black as a conductive material, and a CMC solution as a binder, adding graphite and a conductive material to the CMC solution, adjusting the amount of solvent (water) so that the weight ratio of the active material, the conductive material, and the binder is 98:1:1 and the solid content containing the active material, the conductive material, and the binder is 40%, and mixing the resultant at 60 rpm for 1 hour using a TK mixer. The negative electrode was prepared by the following method: under specific coating conditions (coating width: 200 mm, coating speed: 5 m / min, loading: 300 mg / cm 2 ) was applied to one surface of a copper current collector with the manufactured negative electrode slurry, the resultant was dried at 100° C., and rolled.

[0118] By the above method, negative electrodes with the same composition were manufactured using CMC solutions with different cumulative filtration amounts, and the measurement results of the number of surface defects are shown in Table 3.

[0119] [Table 3]

[0120] type W10=454g W10=1020g W10=1408g W10=1700g A 1231 534 364 193 B 30 25 10 3 C 11 3 1 0

[0121] In Table 3, the surface defects are classified into type A, type B, and type C according to the shape and size of the surface defects for surface defect evaluation. Type A is the case of gray spots different from the normal negative electrode surface, type B is the case of crater-shaped or pinhole-shaped with a width of less than 5 mm, and type C is the case of crater-shaped or pinhole-shaped with a width of more than 5 mm. The number of surface defects of the negative electrode with a total length of 50 m was visually confirmed.

[0122] As shown in Table 3, it can be seen that as the cumulative filtration amount (W10) in 10 minutes increases, the number of negative electrode surface defects decreases. In particular, since C-type surface defects have a greater impact on battery performance degradation than other types, the surface should be carefully managed to avoid such defects. When C-type surface defects exist, blanks are generated in the active material layer in the area corresponding to the defects, the battery capacity decreases, and the resistance increases as much as the blank area. Therefore, the dissolution quality of the binder solution (CMC solution) should be managed so that W10 is 1400 g or more.

[0123] Although Examples 1 and 2 above exemplify the negative electrode binder solution and the negative electrode, the dissolution quality of the positive electrode binder solution and the positive electrode is evaluated using the cumulative filtration amount so that the quality of the positive electrode (eg, surface defects) can be improved.

[0124] From the above results, it can be seen that the dissolution quality is evaluated by the cumulative filtration amount of the binder solution, and the surface defects of the electrode (negative electrode or positive electrode) can be predicted and managed by preparing the electrode slurry (negative electrode or positive electrode slurry) using a binder solution whose cumulative filtration amount determined by the evaluated quality is above a specific value.

[0125] Comparative Example 2

[0126] An 8% PVDF solution was prepared by adding a specific amount of PVDF to an NMP solvent and mixing the resulting mixture for 4 hours using a homogenizer. The PVDF solutions of Comparative Example 2 (Comparative Example 2-1 and Comparative Example 2-2) were prepared by using the same mixing conditions except that the mixing temperatures were set to 70°C and 50°C, respectively.

[0127] The prepared PVDF solution was filtered through a nylon mesh filter by a conventional evaluation method to observe the amount of impurities in the filter.

[0128] Figure 3 The amount of foreign matter in the filter obtained by applying the conventional nylon mesh filtration evaluation method is shown. Figure 3 A shows the amount of impurities measured for Comparative Example 2-1 at a mixing temperature of 70°C, Figure 3 B shows the amount of impurities measured for Comparative Example 2-2 at a mixing temperature of 50°C. Since all other preparation conditions of the adhesive solution were the same except for the mixing temperature, it was expected that the amount of impurities in Comparative Example 2-1 mixed at a higher temperature would be less. Figure 3 As shown, Figure 3 The number of impurities in Comparative Example 2-1 shown in A is 28, Figure 3 The number of impurities of Comparative Example 2-2 shown in B is 21, indicating that the number of impurities of Comparative Example 2-1 mixed at a higher temperature is larger.

[0129] It can be seen that it is difficult to quantitatively evaluate the dissolution quality of the adhesive solution because it is impossible to determine which solution is defective or the quality of the adhesive solution through the conventional nylon mesh filtration evaluation method.

[0130] Example 3 and Comparative Example 3

[0131] By using Figure 1 The system shown was used to filter the solutions of Comparative Example 2-1 and Comparative Example 2-2 to measure the flow reduction rate (%), which was set as Example 3 and Comparative Example 3-1, respectively. In addition, another PVDF solution was prepared under the same mixing conditions as Comparative Example 2-2 at the same mixing temperature (50° C.), which was set as Comparative Example 3-2, and their flow reduction rates were also measured.

[0132] The online filter used to measure the flow reduction rate is an F1 series online filter (Heluco), and the filter element used is a stainless steel depth filter. The pore size of the online filter used in this article is 2 μm. An electronic scale (GP30K electronic scale, AND company) was used to measure the flow rate of the filtered solution, and the measurement results of the flow reduction rate over time are shown in Figure 4 .

[0133] like Figure 4 As shown in FIG. 1 , it can be seen that the flow rate reduction (flow rate reduction rate) changes very little over time compared to the initial flow rate of Example 3, which was filtered using a closed in-line filter system after mixing at 70°C. The initial flow rate of Example 3 was 5.71 g, but Figure 4 In A, the flow rate after 2 hours is about 5.20g, at which time about 91% of the initial flow rate is maintained, and the flow reduction rate is only 9%. Then the flow rate of the PVDF solution of Example 3 slowly decreases, so even after 10 hours, it is still 88% of the initial flow rate, and the flow reduction rate is only 12%. Therefore, the flow reduction rate of the adhesive solution of Example 3 is very low, and it can be determined to be good. Taking into account the test time, the overall quality can be determined by the flow reduction rate relative to the initial flow rate after 2 hours. That is, as in Example 3, a solution with a flow reduction rate of less than 10% relative to the initial flow rate after 2 hours can be determined to have good quality. However, depending on the type of solution, mixing conditions or required electrode characteristics, the time and % value for determining the flow rate reduction rate can vary. For example, the flow reduction rate after filtering for 4 hours, 6 hours and 8 hours can also be used as a standard for determining the dissolution quality of the adhesive solution. In addition, the flow rate when the flow rate is reduced to 80% of the initial flow rate, that is, the flow reduction rate is 20%, can be used as a standard for determining the dissolution quality. Therefore, as a criterion for a good adhesive solution, a solution such as the solution of Example 3, in which the flow rate decreases by no more than 20% despite the passage of time, can be defined as a high-quality solution.

[0134] On the other hand, the initial flow rate of the solution of Comparative Example 3-1 was 4.28, and the flow rate after 2 hours was 0.80, resulting in a flow rate reduction rate of 82%. In addition, after passing through the filter for 10 hours, the filter was clogged with undissolved matter, so that the solution hardly flowed.

[0135] The solution of Comparative Example 3-2 also had an initial flow rate of 4.96, but the flow rate after 2 hours was 1.90, resulting in a flow rate reduction rate of 62%. Even after 10 hours of filtration, the solution of Comparative Example 3-2 hardly flowed because the filter was clogged with undissolved matter. Therefore, the solutions of Comparative Examples 3-1 and 3-2 can be determined to be of poor quality.

[0136] As can be seen from the above, when the dissolution quality of the solution is evaluated by the flow rate reduction rate according to the method of the present invention, the dissolution quality of the secondary battery binder solution can be quantitatively evaluated.

[0137] Example 4 and Comparative Example 4

[0138] In order to evaluate the quality characteristics of electrode slurry based on the flow reduction rate (dissolution quality) of PVDF solution, PVDF solutions of Example 3 and Comparative Examples 3-1 and 3-2 with the same concentration but different flow reduction rates were prepared at different mixing temperatures of 70°C, 50°C and 50°C.

[0139] The positive electrode slurry was prepared by preparing Li[Ni 0.6 Mn 0.2 Co 0.2 ]O2, carbon black as a conductive material and a PVDF solution as a binder, the active material and the conductive material are added to the PVDF solution, the amount of solvent (NMP) is adjusted so that the weight ratio of the active material, the conductive material and the binder is 96.5:1.5:2, the solid content of the active material, the conductive material and the binder is 65%, and the resultant is mixed with a homogenizer for 1 hour. The positive electrode is manufactured by coating the slurry on an aluminum foil with a thickness of 20 μm, drying and pressing.

[0140] According to the above method, positive electrode slurries and positive electrodes of the same composition were respectively manufactured using PVDF solutions of Example 3, Comparative Example 3-1 and Comparative Example 3-2, which had different flow rate reduction rates relative to the initial flow rate after 2 hours. The positive electrode slurry and positive electrode prepared with the PVDF solution of Example 3 were set as Example 4, and the positive electrode slurry and positive electrode prepared with the PVDF solutions of Comparative Example 3-1 and Comparative Example 3-2 were set as Comparative Example 4-1 and Comparative Example 4-2, respectively. The measurement results of the viscosity of the positive electrode slurries of the examples and comparative examples and the bonding strength of the corresponding positive electrodes are shown in the following Tables 4 and Figure 5 middle.

[0141] [Table 4]

[0142] Cathode / Cathode Slurry Example 4 Comparative Example 4-1 Comparative Example 4-2 Slurry viscosity (cps) 19,516 20,805 23,906 Adhesion strength (gf / 20mm) 46.9 34.9 32.3

[0143] The viscosity was measured using a Brookfield viscometer (model: LVDV2T) at 25°C and a shear rate of 12 rpm.

[0144] The adhesive strength of the positive electrode was measured in the following manner: the positive electrode was cut into a size of 15 cm × 2 cm, the coated surface of the positive electrode active material layer of the positive electrode was adhered to a slide glass with a double-sided tape, and the force (gf / mm; peel strength) when the tape was peeled off from the sample was measured by pulling one end of the sample positive electrode at a rate of 100 mm / min and a peeling angle of 90° using a universal testing machine (UTM).

[0145] As shown in Table 4, it can be seen that the viscosity of Comparative Examples 4-1 and 4-2, which are positive electrode slurries prepared using binder solutions mixed at 50° C., increased by 6.6% and 22%, respectively, compared to the viscosity of the binder solution of Example 4 mixed at 70° C.

[0146] In addition, it can be seen that the bonding strength of the positive electrodes of Comparative Examples 4-1 and Comparative Examples 4-2 is reduced by 26% and 31%, respectively, compared with the positive electrode of Example 4 prepared with the binder solution mixed at 70°C. That is, because Example 4 involves a positive electrode prepared with a high-quality binder solution (Example 3-1) having a flow reduction rate of 10% or less relative to the initial flow rate after the second time period (2 hours), the electrode quality is excellent. That is, the viscosity of the electrode slurry of Example 4 is relatively low, but the electrode adhesion is excellent. On the other hand, it is expected that the viscosity of the positive electrode slurries of Comparative Examples 4-1 and Comparative Examples 4-2 prepared with the binder solutions of Comparative Examples 3-1 and Comparative Examples 3-2 having a high flow reduction rate after 2 hours increases, thereby reducing the fluidity of the electrode slurry and resulting in poor coating. In addition, it can be seen that the bonding strength of the positive electrodes prepared with the positive electrode slurries of Comparative Examples 4-1 and Comparative Examples 4-2 is also significantly reduced compared with Example 4.

[0147] On the other hand, since Comparative Example 4-1 and Comparative Example 4-2 were prepared using binder solutions mixed under the same temperature conditions, it is difficult to determine which binder solution has good quality or which solution can produce a good electrode (slurry) only by the temperature conditions. However, as described above, in the present invention, the dissolution quality of the solution can be quantitatively evaluated using the flow reduction rate. Therefore, it can be seen that even for binder solutions prepared under the same temperature conditions, not only can their dissolution quality be quantitatively evaluated, but also the quality characteristics of the electrode (slurry) prepared therefrom can be predicted and managed.

[0148] Although the above-mentioned Examples 3 and 4 are examples of positive electrode binder solutions and positive electrodes, the flow reduction rate can also be used to evaluate the dissolution quality of negative electrode binder solutions and negative electrodes to improve the quality of the negative electrode (such as viscosity or electrode adhesion, etc.).

[0149] From the above results, it can be seen that by preparing electrode slurry (negative electrode or positive electrode slurry) using a binder solution whose dissolution quality has been evaluated by the flow reduction rate of the binder solution and whose flow reduction rate has been determined to be below a specific value, the surface defects of the electrode (negative electrode or positive electrode) can be predicted and managed.

[0150] In addition, the cumulative filtration amount and the flow reduction rate of the binder solution can be measured simultaneously to more comprehensively evaluate the dissolution quality of the corresponding solution. That is, when both parameters are excellent, the binder solution can be evaluated as having the best quality. In addition, a binder solution in which only one of the two parameters reaches the target value can be evaluated as a binder solution that can be used normally. Even if a binder solution in which both parameters do not reach the target value may be evaluated as having good quality by conventional evaluation methods, it can also be evaluated as a binder solution that is not suitable for manufacturing electrodes.

[0151] Therefore, according to the evaluation system and evaluation method of the dissolution quality of the secondary battery electrode binder solution of the present invention, the discrimination ability of the binder solution quality evaluation can be improved.

[0152] As mentioned above, the present invention has been described in more detail with reference to the accompanying drawings and the above-mentioned embodiments. However, since the configuration of the embodiments described herein is provided only as the most preferred embodiment and does not represent the entire technical spirit of the present invention, it should be understood that there may be multiple equivalents and modifications that can replace them when submitting this application.

[0153] (Explanation of symbols)

[0154] 1: Adhesive solution

[0155] 10: Pressure Vessel

[0156] 11: Pressure gauge

[0157] 12: Solution discharge conduit

[0158] 12a: Part of the catheter

[0159] 13: On / off valve

[0160] 20: Pressure medium source

[0161] 21: Pressure medium on / off valve

[0162] 22: Pressure medium supply pipeline

[0163] 30: Inline filter

[0164] 31: Filter component

[0165] 32: Elastic component

[0166] 33: Shell

[0167] 34: Washer

[0168] 40: Flow measurement components

[0169] 41: Electronic scale

[0170] 42: Flow measurement components

Claims

1. A system for evaluating the dissolution quality of a binder solution for a secondary battery electrode, the system comprising: a pressure vessel for containing the binder solution; a pressure medium source for supplying a pressure medium of a predetermined pressure to the pressure vessel; a filter connected to the pressure vessel via a conduit; as well as A flow measurement means for measuring at least one of a) and b) of the binder solution passing through the filter when the binder solution in the pressure vessel is transferred to the filter and filtered by the pressure medium supplied to the pressure vessel: a) cumulative filtration volume during the first period of time; and b) The flow rate reduction rate after the second time period relative to the initial flow rate.

2. The system of claim 1, wherein the conduit extends into the pressure vessel and an end of the conduit is mounted near the bottom of the pressure vessel.

3. The system of claim 1, wherein the filter is an in-line filter installed in series with the conduit.

4. The system of claim 3, wherein the in-line filter comprises a filter member, an elastic member pressurizing the filter member, and a housing accommodating the filter member and the elastic member.

5. A method for evaluating the dissolution quality of a binder solution for a secondary battery electrode, the method comprising: Putting a predetermined amount of adhesive solution into the pressure vessel; transferring the binder solution to a filter by supplying a pressure medium of a predetermined pressure to the pressure vessel; filtering the binder solution through the filter; as well as At least one of a) and b) is measured on the binder solution passing through the filter: a) cumulative filtration volume during the first period of time; and b) The flow rate reduction rate after the second time period relative to the initial flow rate.

6. The method of claim 5, wherein the binder solution is stored and transferred from the pressure vessel in a system closed to the outside until the a) cumulative filtration amount or the b) flow reduction rate is measured.

7. The method of claim 6, wherein the binder solution is transferred to the filter along a conduit extending into the pressure vessel and having one end mounted near the bottom of the pressure vessel.

8. The method of claim 7, wherein the binder solution is filtered through an in-line filter installed in series with the conduit.

9. The method of claim 5, wherein the binder as the solute of the binder solution comprises one or more selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, hydroxyethyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, polyacrylic acid, EPDM, sulfonated EPDM, polytetrafluoroethylene (PTFE), nitrile rubber, styrene-butadiene rubber (SBR) and acrylic rubber.

10. The method of claim 5, wherein the solvent of the adhesive solution comprises: One or more organic solvents selected from N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone and dimethylacetamide, or water.

11. The method of claim 5, wherein the binder solution comprises a carboxymethyl cellulose (CMC) solution in which a predetermined content of carboxymethyl cellulose (CMC) is dissolved in water. 12 . The method of claim 5 , wherein the binder solution comprises a polyvinylidene fluoride (PVDF) solution in which a predetermined content of polyvinylidene fluoride (PVDF) is dissolved in N-methylpyrrolidone (NMP).

13. The method of claim 5, wherein the cumulative filtration volume in the first time period is the cumulative filtration volume 10 minutes after filtration.

14. The method of claim 5, wherein the flow rate reduction rate relative to the initial flow rate after the second period of time is the flow rate reduction rate relative to the initial flow rate after 2 hours.

15. A method for producing an electrode slurry for a secondary battery, the method comprising: The method for evaluating the dissolution quality of a binder solution for secondary battery electrodes according to claim 5 is to prepare a binder solution that satisfies at least one of a1) and b1); as well as The electrode slurry is made by mixing the electrode active material and the conductive material with the binder solution: a1) cumulative filtration volume in a first time period exceeding a predetermined volume; and b1) a flow rate reduction rate relative to the initial flow rate after a second period of time below a predetermined value.

Citation Information

Patent Citations

  • Control system and control device for patrol and moving out, and operation method thereof

    KR1020210041337A

  • Tower lift

    KR1020210041343A

  • Carboxymethylcellulose for electrode in rechargeable battery with nonaqueous electrolyte, salt thereof, and aqueous solution thereof

    CN105140522A

  • Pure water producing apparatus

    JP2014104401A